COVID-19 vaccines effectiveness against symptomatic disease and severe outcomes, 2021–2022: a test-negative case–control study. (May 2023) - Brazete, C.; Brazete, J.; Alves, F.; Aguiar, A.; Gonçalves, A.M.; Cardoso, M.; Sá, L.; Gonçalves, E.; Pinto, M.; Duarte, R.
Abstract: Objectives: This study evaluated the effectiveness of COVID-19 vaccines in preventing symptomatic and severe disease. Study design: This was an observational test-negative case–control study. Methods: Study participants were adults with at least one symptom included in the World Health Organization COVID-19 definition who sought health care in a public emergency department between 1 November 2021 and 2 March 2022 (corresponding with the fifth pandemic wave in Portugal dominated by the Omicron variant). This study used multivariable logistic regression models to estimate and compare the odds ratio of vaccination between test-positive cases and test-negative controls to calculate the absolute and relative vaccine effectiveness. Results: The study included 1059 individuals (522 cases and 537 controls) with a median age of 56 years and 58% were women. Compared with the effectiveness of the primary vaccination scheme that had been completed ≥180 days earlier, the relative effectiveness against symptomatic infection of a booster administered between 14 and 132 days earlier was 71% (95% confidence interval [CI]: 57%, 81%; P < 0.001). The effectiveness of the primary series against symptomatic infection peaked at 85% (95% CI: 56%, 95%) between 14 and 90 days after the last inoculation and decreased to 34% (95% CI: −43%, 50%) after ≥180 days. Conclusions: Despite the known immunological evasion characteristics of the Omicron variant, results from this study show that vaccine effectiveness increases after booster administration. COVID-19 vaccine effectiveness decreases to less than 50% between 3 and 6 months after completion of the primary cycle; therefore, this would be an appropriate time to administer a booster to restore immunity.